1994
DOI: 10.1152/ajpheart.1994.266.4.h1332
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-sensitive CO2 reactivity of cerebral arterioles is restored by vasodilator prostaglandin

Abstract: To investigate the role of vasodilator prostanoids in the CO2-induced relaxation of cerebral arterioles, the present study examined the effect of exogenous prostaglandin (PG) E2 and nonprostanoid vasodilators, adenosine and sodium nitroprusside, on the indomethacin-impaired pial arteriolar response to CO2 in newborn piglets. Reactivity of pial arterioles (52-131 microns diam) was determined using a closed cranial window with intravital microscopy. Cortical prostanoid synthesis was assessed by analyzing for sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 19 publications
4
40
0
Order By: Relevance
“…The magnitude of the relaxation was very similar to that which we observed previously in phenylephrine preconstricted aortic rings (Sweeney et al 1998a) and is in agreement with the widely reported relaxant effect of acidosis in systemic vessels (Tobian et al 1959;Kontos et al 1977a,b;Wagerle & Mishra, 1988;Nielsen et al 1991;Austin & Wray, 1993;Fukuda et al 1993;Wagerle & Degiulio, 1994;Tian et al 1995;Peng et al 1998). In isohydric hypercapnia, however, the tension in PGF2á preconstricted carotid arteries was unchanged.…”
Section: Resultssupporting
confidence: 90%
“…The magnitude of the relaxation was very similar to that which we observed previously in phenylephrine preconstricted aortic rings (Sweeney et al 1998a) and is in agreement with the widely reported relaxant effect of acidosis in systemic vessels (Tobian et al 1959;Kontos et al 1977a,b;Wagerle & Mishra, 1988;Nielsen et al 1991;Austin & Wray, 1993;Fukuda et al 1993;Wagerle & Degiulio, 1994;Tian et al 1995;Peng et al 1998). In isohydric hypercapnia, however, the tension in PGF2á preconstricted carotid arteries was unchanged.…”
Section: Resultssupporting
confidence: 90%
“…In this species, hypercapnia-induced dilation of pial arterioles was impaired after light/dye endothelial injury, indicating endothelial involvement (14,26). Additionally, vasodilation was found to be one of the numerous COX-dependent responses since inhibition of COX with indomethacin consistently abolished the vascular response (9,27,28). The role of COX-derived prostanoids in the mechanism of vasodilation to hypercapnia has been proposed as a "permissive role" since supplementation of exogenous prostacyclin could restore arteriolar responsiveness following indomethacin or light-dye injury (9,26).…”
Section: Cox-dependent Vascular Responses In Pigsmentioning
confidence: 77%
“…11 Ibuprofen decreases pial vessel diameter in newborn pigs but does not affect the CO 2 reactivity of these vessels. 24 Indomethacin may therefore change the vessel reactivity through affecting other processes than the prostaglandin synthesis, 27 but it may also be a more potent drug in inhibiting cyclo-oxygenase. 28 The inhibiting effect of indomethacin on CO 2 reactivity in cerebral vessels have been reversed by directly adding prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…28 The inhibiting effect of indomethacin on CO 2 reactivity in cerebral vessels have been reversed by directly adding prostaglandins. 24 Thus, it is likely that prostaglandins at least facilitate CO 2 induced vasodilation. 24 We have previously shown that measurements of the oxygen tension in the normal pig vitreous can be obtained using the 20 mm oxygen electrodes, employed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation